The relationship between burnout levels and mindfulness of university students-athletes - Serkan Necati Metin; Kamil Uzgur; Yağmur Akkoyunlu; Nurettin Konar (Physical Education of Students)
Background and Study Aim. This study was conducted to examine the relationship between burnout levels and mindfulness of students who are active athletes.